Analisis Analisis Faktor yang Berhubungan dengan Kejadian Diare pada Anak - Agus Tuang (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Abstract. Introduction; Diarrhea is a major problem because as a cause of death it can cause extraordinary events. Aim; This study aims to determine the factors associated with the incidence of diarrhea in children. Methodology; This research uses a descriptive-analytic research method with a cross-sectional study approach. The population in this study were all mothers of school-age children (6-12 years) with a total sample of 66 children. Results; This study shows the relationship between the availability of clean water (ρ=0,001), handwashing habits (ρ=0,004), food sanitation (ρ=0,024), availability of latrines (ρ=0,000), and waste management (ρ=0,003) with the incidence of diarrhea in children. child. Conclusion; There is a relationship between the availability of clean water, hand washing habits, food sanitation, availability of latrines, and waste management with the incidence of diarrhea in children.